True Umbilical Cord Knot, Nochal Cord and Cord Round Body with Favourable Obstetric Outcome in an Unbooked Elderly Nullipara: A Case Report and Literature Review - E. L., Kotingo; D. O., Allagoa (International Journal For Research In Health Sciences And Nursing, 2016)
Basically, umbilical cord knots in general can be classified as true or loose. True knot of the umbilical cord in contrast to other conditions like nuchal coils and cords around the body, may have significant clinical sequelae. Tightening of umbilical cord knot is a very rare and highly unprecedented complication of pregnancy that can lead to foetal demise or neonatal death. We report a rare case of True umbilical cord knot, nuchal cord and cord round body in Yenagoa, South south Nigeria: A 42 year old unbooked elderly nullipara who presented at 41 weeks and 3 days with Labour pains of 4 hours, Drainage of Liquor of 2 hours and Bleeding per vaginam of 30 minutes. She had an Emergency caesarean section for Abruptio placenta with a live baby and foetal heart irregularity in labour. Intraoperative findings include a bloody liquor, Live female neonate with Apgar score of 4 1 8 5 . Birth weight was 3.4kg. There was no gross congenital anomaly seen. Placenta was fundally located, Placenta weighed 0.7kg. A true umbilical cord knot, nuchal cord and cord round body twice was found. Umbilical cord length was 144 cm. The true knot was 50 cm from foetal insertion and cord was centrally inserted into the placenta with a retroplacenta clot of about 200ml. Currently, our experience on True umbilical cord knot is constrained to incidental postnatal finding. However, until prenatal diagnosis is improved with the use of ultrasonography for True umbilical cord knot, good clinical acumen, intrapartum surveillance and prompt obstetric intervention remain pivotal in the aversion of perinatal mortality.